“You’ve Got the Music in You, Don’t You?" Designing Emotionally Engaging Musical Visualizations - Castro, Mariana; Reinbold, Isabelle; Nunes, Caio; Darin, Ticianne (Anais do Workshop sobre Interação e Pesquisa de Usuários no Desenvolvimento de Jogos (WIPlay); 2024: Anais do III Workshop sobre Interação e Pesquisa de Usuários no Desenvolvimento de JogosDO - 10.5753/wiplay.2024.245474, 2024)
Integrating music and visualization in video games is crucial in enhancing emotional storytelling and immersion. Despite the recognized power of music to evoke emotions, the deliberate combination of music and visual elements to convey specific emotions in video games remains underexplored. This study addresses this gap by proposing a set of design principles to improve the emotional impact of musical visualizations in video games. They were applied and evaluated in two visualizations, and the results showed greater alignment with the intended emotional communication. Our findings give game developers practical insights to create more emotionally engaging visual experiences.